Nutritional status and functional performanceof patients qualified for cardiac pacemaker implantation - Kołodziej , Karolina Elżbieta; Chrobak-Bień, Joanna; Wcisło, Tomasz; Plewka, Michał; Borowiak , Ewa (Nursing in the 21st Century, 2025)
Aim. The aim of the study is to assess nutritional status and the risk of health deterioration, deterioration of functional capacity or death within the next two years in relation to demographics of patients qualified for cardiac pacemaker implantation. Material and methods. The study was conducted on 211 patients aged 65 years or older qualified for cardiac pacemaker implantation. Results. The mean age of the respondents was 78 ± 7.56 years. Most of the respondents of the study group were women. Patients in the age groups 65-74 years and 75-84 years declared similar nutritional status. The risk of health deterioration, functional capacity and death increased with age. Conclusions. The risk of malnutrition and diagnosed malnutrition were mostly observed in patients aged 85 years and older. The growing risk of significant deterioration of health and functional capacity in patients qualified for cardiac pacemaker implantation were attributed to aging, being unmarried, less educated and having poorer nutritional status. Improvement of the nutritional status, particularly in people at the age of 85 years or older, qualified for cardiac pacemaker implantation, is one of the key factors contributing to a lower risk of significant deterioration of health.